Designing secure sensor networks. - Shi, E. (IEEE Wireless communications)
Sensor networks are expected to play an essential role in the upcoming age of pervasive computing. Due to their constraints in computation, memory, and power resources, their susceptibility to physical capture, and use of wireless communications, security is a challenge in these networks. The scale of deployments of wireless sensor networks require careful decisions and trade-offs among various security measures. The authors discuss these issues and consider mechanisms to achieve secure communication in these networks.